Aplicação da álgebra linear no tratamento de imagens - Júnior, Fernando Venancio Aires (Universidade Federal de São Carlos, 2024)
This work explores the application of linear algebra in image processing. We use matrix operations such as addition, multiplication, and convolution to improve image quality. The approach on the spatial and frequency domains, the work illustrates the relevance of mathematical concepts in image processing and their applicability in the interpretation and extraction of visual information.
Applications of Linear Algebra in image processing
Keywords: Álgebra linear; Tratamento de imagens; Domínio de frequência; CIENCIAS EXATAS E DA TERRA::MATEMATICA::MATEMATICA APLICADA::MATEMATICA DISCRETA E COMBINATORIA